The Labour Party and the Nursing Profession - MacDonald, James Ramsay, 1866-1937 (London : The Labour Party (London : Co-operative Print. Society Ltd.), 1927)
1927 1927 1920s 40 pages 40 2. Public health students, with two years' specialised public health and social training (including the preparation for a sanitary inspector's examination), holding the C.M.B. certificate, and having had six months' hospital experience. 3. Social science students of a university, who have specialised in public health work during the latter part of their two or three year course, holding the C.M.B. certificate and having had six months' hospital experience. The two first of these sources of supply are already recognised in the present requirements of the Ministry of Health (Circular M. and C.W. 101). We consider that, on a large staff of health visitors the best results will be probably attained if different members of the staff have greater knowledge than others of particular problems. Given a spirit of friendly co-operation, a greater fund of knowledge will be available for the service of the homes visited than would be possible if all health visitors had one type of training only. The length of training and the qualifications demanded should receive adequate recognition in the amount of the salary received, which should be of such a standard as to attract a suitable type of woman to the profession. There should be a joint body of the Ministry of Health, local authorities and health visitors to settle a scale of salary, and no appointment should be sanctioned by the Ministry which is not made in accordance with the recognised scale. Years of service with a previous local authority, other things being equal, should be taken into account in determining the salary of a health visitor entering the service of another, and such previous service should count for superannuation. At present a health visitor has to begin at the minimum salary with every change of appointment. Holidays, allowances, payment during sickness, should all be standardised in the same way. Superannuation schemes should be made compulsory for all local authorities. In view of the arduous nature of the work, the retiring age should be 55, with the option of continuing to 60, if physically fit. "THE LABOUR MOVEMENT AND THE HOSPITAL CRISIS: A STATEMENT OF POLICY WITH REGARD TO HOSPITALS." Price 1s. post free. "THE HOSPITAL PROBLEM": The Report of a Special Conference of Labour, Hospital, Medical and Kindred Societies held in the Caxton Hall, Westminster, on April 28th and 29th, 1924. Price 6d. post free. The Labour Party. 33, Eccleston Square, London, S.W.1 (7/27/5)—Co-operative Printing Society Limited, Tudor Street, New Bridge Street, London, E.C.4.—96. 126/TG/RES/X/1036A/14